The structure of Toho1 β‐lactamase in complex with penicillin reveals the role of Tyr105 in substrate recognition. Issue 12 (7th November 2016) - Langan, Patricia S.; Vandavasi, Venu Gopal; Weiss, Kevin L.; Cooper, Jonathan B.; Ginell, Stephan L.; Coates, Leighton
Abstract : The role of the conserved residue Tyr105 in class A β‐lactamases has been the subject of investigation using both structural studies and saturation mutagenesis. Both have shown that while it does not need to be strictly conserved for activity, it is important for substrate recognition. With this in mind we determined the crystal structure of Toho1 β‐lactamase at 15 K to 1.10 Å resolution in complex with penicillin. As expected a ring‐opened penicillin molecule bound to Ser70 the catalytic nucleophile, can clearly be seen in electron density in the active site. In addition to the trapped penicillin, however, are two additional intact ring‐closed penicillin molecules, captured by the enzyme through noncovalent interactions at the edge of the active site. Abstract : To investigate the role of the conserved residue Tyr105 in class A β‐lactamases, the crystal structure of Toho1 β‐lactamase complexed with penicillin was solved at 15 K to 1.10 Å resolution. Visualization of the complex reveals the interactions necessary for substrate recognition and binding, and provides insight into how these interactions may drive enzyme function.